Extração de ouro contido em minério de baixo teor empregando pilhas de lixiviação com cianeto - Fernanda Sofia Alves Finco (2013)
The results obtained in the heap leach industrial processing of low grade gold ore from São Vicente Mine (MT), owned by Mineração Apoena S.A., showed high cyanide consumption. In addition, revealed some unpredictability in the gold recovery. This dissertation presents the experimental results for the gold extraction from cyanide leaching tests on three pilot scale units: giant columns, small columns and bottle on rolls. The parameters studied in the column tests were the cyanide concentration (ppm) in the feed solution and the application rate (L.h-1.m-2) of the feed solution. In the bottle roll tests was also evaluated the amount of calcium hydroxide dosed in the ore for determining the cyanide consumption and the impact on gold extraction. The performance of these tests also allowed the determination of operating conditions considered optimal for the cyanide concentration in the feed solution and the application rate of the feed solution of the heap leach aiming, mainly, at reducing the costs. With the obtained results, the cyanide consumption and the percentage of gold extraction were calculated for each test, and thus, the optimized parameters were determined: dosage of 1.5 kilogram of calcium hydroxide per tonnage of ore, application rate of feed solution of 6 Lh-1.m-2 and concentration of 200 ppm of cyanide.